Examining the Roles of the European Union, France and the United States in Combating Terrorism in the Sahel - Abraham, E. (University of Ghana, 2020)
Global security has taken a new dimension since the horrific incident that took place during the September 11, 2001 terrorist attack in the United States of America. The global war against terror took effect after this incident in order to put an end to the threats terrorism poses. The African continent has not been spared in the rise of terrorism. The Sahel region of the continent has become a hotspot of terrorism for almost a decade now. Countries like Mali, Nigeria and Burkina Faso have been the major crisis corridors of the region. This has drawn global attention and interventions from the international community even outside the continent. After almost a decade of foreign interventions in the region, the situation seems unchanging. For this reason, the study analyzes the situation in the region and the reason for a prolonged crisis in the midst of several interventions. It investigates the root causes of terrorism in the region as well as what causes further exacerbations even in the midst of interventions. The investigations reveal that most of the so-called terrorist groups in the region are mostly aggrieved interest groups, either ethnic or religious in nature, who use radical means to register their plights when their grievances are unaddressed. The involvements and interventions of foreign players especially through military means is resulting in further worsening the situation in the region as these groups retaliate even more. The major international players at the fore-front of the fight in the region are; the European Union, France and the United States. Even though these players have played some positive roles, these radical groups keep carrying out operations in the region in a form of retaliation to these players. The research also reveals that resource reserves such as uranium, oil, ore, etc…which are in large deposits, are the major reason for not only the interventions of these players but their prolonged stay in the region. Their personal interests are tied to the vase supply of these resources and thus use their interventions in the region as a means to also secure a share of these reserves. The research recommends some of the necessary steps that could be taken in order to deal with the situation in the region. A major means is to strengthen focus more on negotiations with aggrieved groups rather than the current focus on military means. It also recommends that regional bodies such as the African Union (AU), the Economic Community of West African States (ECOWAS) should be at the forefront with the United Nations (UN) in dealing with the situation in the region, rather than leaving them in the hands of individual countries and other regional bodies who may fall prey to their personal interests in the region.
MA. International Affairs
Keywords: European Union; France; United States of America; Terrorism; Sahel; Global security; African continent; Economic Community of West African States (ECOWAS); African Union (AU); United Nations (UN)